1977
DOI: 10.1002/1097-0142(197705)39:5<2280::aid-cncr2820390548>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the breast.The prognostic significance of extranodal extension of axillary disease

Abstract: A retrospective study to determine the effect of extranodal axillary disease on prognosis in invasive carcinoma of the breast was undertaken in a series of 152 cases. It was found that extranodal disease has an unfavorable effect on prognosis in those patients with three or less involved axillary nodes and no effect on prognosis in those patients with four or more involved axillary nodes. Extranodal axillary disease was found to have no influence on the interval between surgery and initial recurrence nor on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 8 publications
0
26
0
3
Order By: Relevance
“…There have been many reports of extranodal invasion, but few related to gastric cancer. It is well known that extranodal invasion is an important indicator of poor prognosis in cancers of the pharynx, larynx, thyroid, lung, and breast [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of extranodal invasion, but few related to gastric cancer. It is well known that extranodal invasion is an important indicator of poor prognosis in cancers of the pharynx, larynx, thyroid, lung, and breast [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…One hundred forty-three cases treated by one of the authors (W.L.D.) were identified as meeting the following criteria: (1) a minimum of 1 year follow-up after treatment, (2) no previous record of cancer (except skin carcinoma), (3) absence of systemic metastases at the time of initial treatment, (4) treatment with a unilateral modified radical mastectomy and a level I1 or I11 axillary lymph node dissection, and (5) available histologic slides with one or more involved axillary lymph nodes on routine sections.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that assessment of extranodal extension (ENE) in patients who are node positive may provide prognostic information in certain human epithelial malignancies, including breast cancer (10,11), squamous cell carcinoma of the vulva (12,13), gastric carcinoma (14), and squamous carcinoma of the head and neck (15)(16)(17)(18)(19)(20)(21). Others refuted the significance of ENE (22)(23)(24)(25)(26). ENE is a frequent histologic finding in lymph nodes with prostate cancer, but its prognostic significance has not been established.…”
mentioning
confidence: 99%